Atomic‐Scale Mechanism of Spontaneous Polarity Inversion in AlN on Nonpolar Sapphire Substrate Grown by MOCVD. Issue 16 (10th February 2022) - Liu, Zhiqiang; Liu, Bingyao; Ren, Fang; Yin, Yue; Zhang, Shuo; Liang, Meng; Dou, Zhipeng; Liu, Zhetong; Yang, Shenyuan; Yan, Jianchang; Wei, Tongbo; Yi, Xiaoyan; et al.
Abstract: The performance of nitride devices is strongly affected by their polarity. Understanding the polarity determination and evolution mechanism of polar wurtzite nitrides on nonpolar substrates is therefore critically important. This work confirms that the polarity of AlN on sapphire prepared by metal–organic chemical vapor deposition is not inherited from the nitrides/sapphire interface as widely accepted, instead, experiences a spontaneous polarity inversion during the growth. It is found that at the initial growth stage, the interface favors the nitrogen‐polarity, rather than the widely accepted metal‐polarity or randomly coexisting. However, the polarity subsequently converts into the metal‐polar situation, at first locally then expanding into the whole area, driven by the anisotropy of surface energies, which results in universally existing inherent inverse grain boundaries. Furthermore, vertical two‐dimensional electron accumulation originating from the lattice symmetry breaking at the inverse grain boundary is first revealed. This work identifies another cause of high‐density defects in nitride epilayers, besides lattice mismatch induced dislocations. These findings also offer new insights into atomic structure and determination mechanism of polarity in nitrides, providing clues for its manipulation toward the novel hetero‐polarity devices. Abstract : For the first time, the growth of nitride on sapphire by metal–organic chemical vapor deposition can be monitored layer‐by‐layer, starting at the substrate, to observe the inverse domain boudary formation and the evolution of the polarity inversion. This work offers a breakthrough in the understanding of the underlying mechanism that dictates the polarity of the nitride epilayer.